OMPHE-VIA (Obedient Male Partner in Health-Education and Engagement for Visual Inspection with Acetic Acid Examination) Model Was Solution to Save Cervical Cancer - Ferdinal Ferry; RIzanda Machmud; Soetrisno Soetrisno; Adang Bachtiar (Universitas Andalas, 2023)
Background: VIA screening is very suitable for developing countries such as Indonesia, because the technique is easy, simple, low cost/cheap, high sensitivity, fast and accurate for early detection of cervical cancer. The coverage of early detection in Indonesia is <5% so that many cases of cervical cancer are found to be at an advanced stage and often cause death in women.Methods: This study uses a mix-method study approach with a sequential exploratory approach. The research was carried out sequentially with qualitative methods first (interviews and FGDs), then continued with quantitative methods. In this study, the sampling technique used was multi-stage random sampling in 7 selected sub-districts.Results: The variable perception of vulnerability with a good perception of vulnerability have a 2.64 times greater risk of carrying out an VIA examination. In multivariate modeling, knowledge is the most dominant variable because it has the largest POR of 6.3, which means the N-Gain value is in the medium category with a fairly effective interpretation of the effectiveness of the module, namely an increase in knowledge of 63.86% after being given education using the OMPHE-VIA module. Conclusion: Based on the implementation of the OMPHE-VIA module, it was found that there was an increase in the average value of knowledge, before and after the education was given. It was also found that there was a significant difference in knowledge, and husband's support, construct between before and after the education was given using the OMPHE-VIA module.